Pengaruh Parameter Pada Mesin CNC Laser Cutting Terhadap Kualitas Hasil Pemotongan Pada Material Sheet Metal di PT. XYZ: The Influence of CNC Laser Cutting Machine Parameters on the Cutting Quality of Sheet Metal at PT. XYZ - Mochammad Rajib El Atros; Kardiman; Boni Sena; Fauzan Hibatullah; Mohadly Satya Permadi (Universitas Pendidikan Ganesha, 2025)
The advancement of the manufacturing industry demands the use of precise, efficient, and highly competitive cutting technology, one of which is CNC Laser Cutting. This study aims to analyze the influence of cutting parameters, such as cutting speed, laser power, focus distance (focusline), nozzle distance, and gas pressure, on the cutting quality of sheet metal made of SUS 304 and Aluminum. The research method includes direct experiments at PT. XYZ with variations in CNC laser machine parameters to evaluate surface roughness, dimensional accuracy, and edge quality of the cut. The results indicate that a higher cutting speed and optimal laser focus improve precision and cutting cleanliness. Nitrogen gas is more effective for cutting SUS 304 and Aluminum compared to other gases. The proper selection of the nozzle also plays a role in maintaining gas flow stability and preventing cutting defects. Additionally, the interaction between cutting speed and laser power significantly impacts the final result. The study concludes that an optimal combination of parameters produces cleaner, more precise, and more efficient cuts, thereby enhancing quality and productivity in the sheet metal industry. Therefore, selecting the appropriate parameters is crucial to achieving the best cutting results and minimizing production defects.